Self Regulation, Self Esteem, dan Self Concept Berpengaruh Terhadap Prestasi Belajar Matematika Peserta Didik - Ummi Rofika Hasan; Fitriani Nur; Ulfiani Rahman; Suharti Suharti; Eka Damayanti (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study was to determine the effect of self regulation, self esteem and self concept. These independent variables are factors within students who have an important role in the learning process. So that the factors in these students become the core in this research study. This type of research is ex post facto involving grade VIII students of SMPN 5 Makassar with a total sample of 168 students. Data collection techniques used questionnaire instruments of self regulation, self esteem and self concept and documentation data in the form of student achievement scores that had passed the validation process. Furthermore, the collected data were analyzed by using multiple linear regression after passing the prerequisite test process. The conclusion of this study shows that self-regulation, self-esteem and self-concept together have an effect on the learning achievement of class VIII students of SMAN 5 Makassar with a large influence of 90.2% and the remaining 9.8% is influenced by other factors. This shows that the factors from within these students have an important role in the success of students in the learning process.